Pengaruh Kepemimpinan Digital, Pemasaran Digital, dan Kredibilitas Influencer terhadap Purchase Intention Wardah pada Konsumen Gen Z di Indonesia dengan Citra Merek sebagai Pemoderasi - Fitri Noviana; Muhammad Junaid Kamaruddin (Journal of Economics and Management Scienties, 2026)
This study aims to examine the influence of digital leadership, digital marketing, and influencer credibility on purchase intention for Wardah products among Gen Z consumers in Indonesia, using brand image as a moderating variable. To deepen our understanding of the factors that shape purchase intention in the digital age, it is important to ensure that halal cosmetics marketing strategies have a significant impact on younger age groups. This study employs a quantitative approach using the Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. Data were collected via a questionnaire survey involving 130 respondents, comprising high school/vocational school students, college students, and the general public who have used Wardah products. The results indicate that digital marketing has a significant and positive influence on purchase intention, trust in influencers also has a significant and positive influence on purchase intention, and brand image also has a significant and positive influence on purchase intention. However, digital leadership does not show a significant influence on purchase intention. Furthermore, brand image does not act as a moderator in the relationship between digital leadership, digital marketing, and influencer credibility with purchase intention. This indicates that the better the digital marketing strategy and the influencer’s credibility, and the more positive the perceived brand image, the higher Gen Z consumers’ purchase intent for Wardah products.